Tegal Duck Male Performa (Anas plantyhinchos javanicus) Starter Phase that Gives Dry Tofu Dregs - Betty Herlina; Nining Suningsih; Syahrul Rohman (Jurnal Peternakan (Jurnal of Animal Science), 2020)
Feed is an important aspect in livestock business. Its role can reach 60-70% of the total production cost so that the use of alternative feed ingredients based on local resources needs to be increased. The purpose of this study was to determine the use of dried tofu dregs in the ration on the performa of starter Tegal male ducks. The research method used is an experimental method. The duck maintenance process lasts for 2 months. The research design used was a Completely Randomized Design (CRD) consisting of 6 treatments and 4 replications. Each test consisted of 4 ducks. The treatments consisted of: P0 = 100% ration, P1 = 90% ration + 10% Dry Tofu Dregs, P2 = 80% Ration + 20% Dry Tofu Dregs, P3 = 70% Ration + 30% Dry Tofu Dregs, P4 = 60% Ration + 40% Dry Tofu Dregs, P5 = 50% Ration + 50% Dry Tofu Dregs. Observed variables: Feed Intake, body weight gain, feed conversion, and mortality. The data obtained were analyzed using Analysis of Variance and Duncan's Multiple Range Test. The results showed that the treatment of the use of dried tofu waste in the ration had a significant effect (P <0.05) on feed intake, and did not significantly affect (P> 0.05) on body weight gain, feed conversion, and mortality. The conclusion from this study the P3 treatment showed an indication that the performa of Tegal ducks was relatively better than other treatments.